Bone metastases and age are associated with earlier dose reductions in metastatic clear-cell renal cell carcinoma patients treated with angiogenesis inhibitors. Issue 6 (2nd November 2019) - Haaker, Lorenz; De Meue, Elisabeth; Wildiers, Hans; Verbiest, Annelies; Dumez, Herlinde; Lerut, Evelyne; Pans, Steven; Albersen, Maarten; Beuselinck, Benoit
ABSTRACT: Background : Metastatic clear-cell renal cell carcinoma (m-ccRCC) patients with bone metastases (BM) treated with vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (TKI) have a poorer outcome compared to patients without BM. We aimed to investigate whether an increased incidence of VEGFR-TKI treatment interruptions and/or dose reductions in patients with BM could explain this difference in outcome. Patients and methods : Retrospective study on m-ccRCC patients treated in first–line with VEGFR-TKI. Analysis of the incidence of treatment interruptions and dose reductions and time-to-event analysis. Study of the correlation with the presence of BM at start of first-line VEGFR-TKIs. Results : Two-hundred-and-five patients were included. In patients with BM, median time-to-dose-reduction was significantly shorter (3 versus 5 cycles; p = 0.005) than in patients without BM. 63% of the total number of cycles was administered at reduced dose, compared to 41% in patients without BM. Age at start of VEGFR-TKI (≤ versus >70 years) was significantly associated with median time-to-dose-reduction (5 versus 3 cycles; p = 0.007). On multivariate analysis, the presence of BM ( p = 0.004; HR 1.82, 95%CI 1.21–2.73) and age at start of VEGFR-TKIs ( p = 0.017; HR 1.65, 95%CI 1.10–2.50) were independently associated with time-to-dose-reduction. Conclusion : In m-ccRCC patients treated with VEGFR-TKIs, dose reductions occurred earlier in patients with BM compared to patients without BM and in elderly patients.